2017
DOI: 10.1186/s12885-017-3529-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of BRAF and NRAS mutations in melanoma: a German study from routine care

Abstract: BackgroundHotspot mutations of the oncogenes BRAF and NRAS are the most common genetic alterations in cutaneous melanoma. Specific inhibitors of BRAF and MEK have shown significant survival benefits in large phase III trials. However, the prognostic significance of BRAF and NRAS mutations outside of clinical trials remains unclear.MethodsThe mutational status of BRAF (exon 15) and NRAS (exon 2 and 3) was determined in melanoma samples of 217 patients with pyrosequencing and Sanger sequencing. The genotypes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
102
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 34 publications
11
102
1
4
Order By: Relevance
“…Some data support that BRAF V600 mutation is an independent favorable prognostic factor (Heppt et al, ). In a recent German trial on 217 melanoma patients (most of them [96%] were Stage I–III patients) BRAF mutation was identified in 40.1% of the samples (Heppt et al, ). BRAF mutation was found to be significantly associated with young age at initial diagnosis, low mitotic activity and seldom acral lentiginous histologic subtype and truncal lesion.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Some data support that BRAF V600 mutation is an independent favorable prognostic factor (Heppt et al, ). In a recent German trial on 217 melanoma patients (most of them [96%] were Stage I–III patients) BRAF mutation was identified in 40.1% of the samples (Heppt et al, ). BRAF mutation was found to be significantly associated with young age at initial diagnosis, low mitotic activity and seldom acral lentiginous histologic subtype and truncal lesion.…”
Section: Discussionmentioning
confidence: 90%
“…Many studies have investigated the association between BRAF mutation and clinicopathological features in melanoma (Akslen et al, ; Ellerhorst et al, ; Heppt et al, ; Hugdahl et al, ; Inumaru et al, ; Maldonado et al, ; Mann et al, ; Meckbach et al, ; Moreau et al, ; Picard et al, ; Shinozaki et al, ). Most of these studies concluded that BRAF mutation was in association with younger age at diagnosis (Heppt et al, ; Hugdahl et al, ; Meckbach et al, ), truncal lesion (Heppt et al, ; Hugdahl et al, ), and the superficially spreading melanoma histotype (Heppt et al, ; Meckbach et al, ), we agree with these findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations